CSLAT: an SLA template for cloud service management. (1st January 2015) - Rane, Dheeraj; Sarma, Monalisa
Service level agreements (SLAs) are used to bind cloud provider for providing services and hence to assure cloud consumer that delivered services are up to the mark. However, most of the cloud SLAs are either static in nature or are concerned only for availability of service leaving major concerns such as performance, security, metering and monitoring, automation, and many more. In this paper, we have reviewed the existing SLA frameworks and then examined their suitability in the context of cloud computing. Next, we discuss the desirable components, which should be considered in cloud SLA. Also, we have identified different parameters that need to be incorporated in each component. Based on this, we put forward a cloud SLA template, which we termed as cloud service level agreement template (CSLAT). This work attempts to provide a clear and formal definition of decisive parameters in cloud computing. The definition will give clear perception of how these parameters should be specified in SLA, so as to avoid any conflict rising due to ambiguity in it. Further, precise monitoring and QoS measurement can be done using the mathematical interpretations given corresponding to parameters. Thus, proposed CSLAT will help in automation of SLA management in cloud computing.